Factors Influencing Consumers' Purchase Intention For Milk Powder In Penang - Yow, Bee Charn (2014)
This study demonstrate the adaption of Theory of Planned Behavior (TPB) to examine how product knowledge, product involvement, perceived benefit, perceived risk and country of origin image influence consumers' purchase intention for milk powder and how consumers' attitude mediates these variables on consumers' purchase intention. The study findings revealed that product knowledge, product involvement and perceived benefit were positively and significantly related to purchase intention.